The α-(1,3)-glucan synthase gene agsE impacts the secretome of Aspergillus niger - Jun Lyu; Costanza Torchia; Harm Post; Juan P. Moran Torres; A. F. Maarten Altelaar; Hans de Cock; Han A. B. Wösten (Antonie van Leeuwenhoek, 2023)
Aspergillus niger is widely used as a cell factory for the industrial production of enzymes. Previously, it was shown that deletion of α-1–3 glucan synthase genes results in smaller micro-colonies in liquid cultures of Aspergillus nidulans . Also, it has been shown that small wild-type Aspergillus niger micro-colonies secrete more protein than large mirco-colonies. We here assessed whether deletion of the agsC or agsE α-1–3 glucan synthase genes results in smaller A. niger micro-colonies and whether this is accompanied by a change in protein secretion. Biomass formation was not affected in the deletion strains but pH of the culture medium had changed from 5.2 in the case of the wild-type to 4.6 and 6.4 for Δ agsC and Δ agsE, respectively. The diameter of the Δ agsC micro-colonies was not affected in liquid cultures. In contrast, diameter of the Δ agsE micro-colonies was reduced from 3304 ± 338 µm to 1229 ± 113 µm. Moreover, the Δ agsE secretome was affected with 54 and 36 unique proteins with a predicted signal peptide in the culture medium of MA234.1 and the Δ agsE, respectively. Results show that these strains have complementary cellulase activity and thus may have complementary activity on plant biomass degradation. Together, α-1–3 glucan synthesis (in)directly impacts protein secretion in A. niger .

Uncovering the abilities of A garicus bisporus to degrade plant biomass throughout its life cycle - Aleksandrina Patyshakuliyeva; Harm Post; Miaomiao Zhou; Edita Jurak; Albert J. R. Heck; Kristiina S. Hildén; Mirjam A. Kabel; Miia R. Mäkelä; Maarten A. F. Altelaar; Ronald P. de Vries (Environmental Microbiology, 2015)
Summary The economically important edible basidiomycete mushroom A garicus bisporus thrives on decaying plant material in forests and grasslands of N orth A merica and E urope. It degrades forest litter and contributes to global carbon recycling, depolymerizing (hemi‐)cellulose and lignin in plant biomass. Relatively little is known about how A . bisporus grows in the controlled environment in commercial production facilities and utilizes its substrate. Using transcriptomics and proteomics, we showed that changes in plant biomass degradation by A . bisporus occur throughout its life cycle. Ligninolytic genes were only highly expressed during the spawning stage day 16. In contrast, (hemi‐)cellulolytic genes were highly expressed at the first flush, whereas low expression was observed at the second flush. The essential role for many highly expressed plant biomass degrading genes was supported by exo‐proteome analysis. Our data also support a model of sequential lignocellulose degradation by wood‐decaying fungi proposed in previous studies, concluding that lignin is degraded at the initial stage of growth in compost and is not modified after the spawning stage. The observed differences in gene expression involved in (hemi‐)cellulose degradation between the first and second flushes could partially explain the reduction in the number of mushrooms during the second flush.